Penerapan Model Pembelajaran Promblem Basic Learning (PBL) Untuk Meningkatkan High Order Thinking Skills (HOTS) - Nirmawati Nirmawati; Sirajuddin Sirajuddin; Syahrul Syahrul; Suryadi Ishak (Journal Peqguruang: Conference Series, 2025)
This study aims to analyze the effectiveness of the application of the Problem Based Learning (PBL) learning model in improving students' Higher Order Thinking Skills (HOTS) in the subject of Plant Agribusiness at SMKN 4 Bulukumba. The research method used is Classroom Action Research (CAR) which consists of two cycles. Data analysis techniques are carried out by processing the results of observations, cycle tests, and interviews. The results of the study showed that the application of the PBL model significantly improved students' high-level thinking skills, with the percentage of classical completeness increasing from 20.69% in cycle I to 89.65% in cycle II. Thus, the PBL model is recommended as an effective learning strategy to improve students' HOTS.